Metallurgical characterization of inconel-625 and waspaloy joints brazed using five Ag, Cu and Ni-base active braze alloys - Shoushounova, Timothiax; Kraft, Ryan T. (University of Wisconsin--Stout. Research Services, 2014)
Many industrial components such as heat exchangers and gas turbines are fabricated by joining a number of simpler units into complex structures. This demands development and demonstration of robust joining technology applicable to a wide variety of materials including alloys that can withstand very high temperatures that are encountered in jet engines, furnaces, combustion cans, and other systems. This research characterized brazed joints of two high-temperature nickelbased alloys for microstructure, composition, and hardness. The purpose was to evaluate the effectiveness of selected brazes and joining conditions to form integral joints that could be further characterized prior to pilot-scale testing and evaluation. Inconel-625 and Waspaloy1 were vacuum brazed using two Ni-base amorphous brazes (MBF2 -20 and MBF-30), two Ti containing Ag-Cu base brazes (Cusil-ABA and Ticusil), and a Cu-base active braze (Cu-ABA) with brazing temperatures in the range 1108-1348 K. All five brazes formed well-bonded metallurgically-sound joints. MBF-20, MBF-30, Ticusil-ABA and Copper-ABA exhibited substantial diffusion and prominent interaction zones whose thickness increased with increasing braze liquidus temperature.Cusil-ABA with the lowest temperature (1108 K) had the smallest reaction layer whereas MBF-30, with the highest temperature (1348 K) had the thickest reaction layer. The interaction zones in Cusil-ABA and Ticusil joints were enriched in titanium and accompanied by Ti depletion and low hardness within braze matrix. The MBF-30 joints revealed the most prominent and most complex reaction layer of all brazes consisting of at least four different regions identified by their Knoop hardness.
Research article with tables, illustrations, and graphs.
Keywords: waspaloy; active braze alloys; metallurgic; Inconel-625; Inconel; Joints (Engineering); Brazing alloys